1992
DOI: 10.1111/j.1365-2958.1992.tb01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of IcsA by cAMP‐dependent protein kinase and its effect on intercellular spread of Shigella flexneri

Abstract: Shigella flexneri, a Gram-negative bacillus belonging to the family Enterobacteriaceae, causes bacillary dysentery in humans by invading colonic epithelial cells. Processes by which epithelial cells, which are not professional phagocytes, may limit the spread of the invading microorganisms are poorly understood. This paper shows that IcsA (VirG), a 120 kDa bacterial outer membrane protein responsible for intracellular and cell-to-cell spread through polymerization of actin, is a major substrate for phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Indeed, d'Hauteville and Sansonetti (8) showed that phosphorylation of IcsA (VirG) by cyclic AMP-dependent protein kinase was abolished when either or both of the Arg residues located at positions 758 and 759 were altered. These mutants expressed a ''super Ics'' phenotype, characterized by an increased capacity to spread from one cell to another during the first 3 h of HeLa cell infection, as well as an increased rate of spreading in the plaque assay or the Serény test (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, d'Hauteville and Sansonetti (8) showed that phosphorylation of IcsA (VirG) by cyclic AMP-dependent protein kinase was abolished when either or both of the Arg residues located at positions 758 and 759 were altered. These mutants expressed a ''super Ics'' phenotype, characterized by an increased capacity to spread from one cell to another during the first 3 h of HeLa cell infection, as well as an increased rate of spreading in the plaque assay or the Serény test (8).…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the Arg-Arg site of in vitro VirG cleavage determined in this study coincided with a sequence encoding a phosphorylation consensus motif, Ser-Ser-ArgArg-Ala-Ser-Ser, located at residues 756 through 762 (8). Indeed, d'Hauteville and Sansonetti (8) showed that phosphorylation of IcsA (VirG) by cyclic AMP-dependent protein kinase was abolished when either or both of the Arg residues located at positions 758 and 759 were altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infection of semiconfluent HeLa cells, the icsA mutant (i) does not diffuse within the cell cytoplasm but rather forms microcolonies near the cell nucleus, (ii) does not elicit the accumulation of polymerized actin on the surface of the bacteria that is observed with the wild-type strain, and (iii) does not spread into adjacent cells (7,20,29,48,49). Upon infection of macaque monkeys, the icsA mutant causes markedly less mucosal destruction than the wild-type strain (40) Labelling of bacteria grown in vitro and bacteria infecting HeLa cells with IcsA antiserum.…”
mentioning
confidence: 99%
“…We have previously constructed shigella mutants that are unable to spread within and between cells (7,20,40). Each of * Corresponding author.…”
mentioning
confidence: 99%